Myopathy in Zidovudine Treated HIV Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Elevations in serum CK levels in 80% of 87 children enrolled in a multi-centered trial of oral zidovudine treatment for symptomatic HIV infection are reported from the Department of Pediatrics, University Medical Center, Durham, NC.